2015
DOI: 10.1007/s40830-015-0035-y
|View full text |Cite
|
Sign up to set email alerts
|

High Strain Rate Compression of Martensitic NiTi Shape Memory Alloys

Abstract: The compressive response of martensitic NiTi shape memory alloys (SMAs) under high strain rate (1200 s -1 ) was investigated on a modified Kolsky (Split Hopkinson) compression bar. The single-loading momentum trapping system ensures precise deformation control (1.4, 1.8, 3.0, 4.8, and 9.6 % strain) and single loading during dynamic compression. With increasing strain, the phase transformation peaks shift toward lower temperatures, while the intensities of these peaks decrease and eventually disappear completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…At low loads, a small area of linear deformation in compression of porous NiTi-(Ar) and NiTi-(N) samples is mainly related to elastic deformation of martensite and its possible reorientation. For NiTi alloys, it has been shown that the mechanism of plastic deformation in compression is mainly related to the formation and migration of dislocations [32][33][34]. Therefore, an increase in load leads to the linearity deviation and a change in the deformation mode to dislocation due to reaching the dislocation yield strength.…”
Section: Resultsmentioning
confidence: 99%
“…At low loads, a small area of linear deformation in compression of porous NiTi-(Ar) and NiTi-(N) samples is mainly related to elastic deformation of martensite and its possible reorientation. For NiTi alloys, it has been shown that the mechanism of plastic deformation in compression is mainly related to the formation and migration of dislocations [32][33][34]. Therefore, an increase in load leads to the linearity deviation and a change in the deformation mode to dislocation due to reaching the dislocation yield strength.…”
Section: Resultsmentioning
confidence: 99%
“…It is confirmed that the flag-shaped hysteric loop of the SMA material can be seen up to 1000s -1 . Many researchers, [9], [11], [20] , [21] , [22], [23], [24], [25] , [26], [27] and [28], studied the behaviour of SMA under low, medium, and high strain rates. The presented studies show that the range of strain rate for which the SMA maintains its energy dissipation capacity characteristics is up to 1000s -1 .…”
Section: Effect Of Strain Ratementioning
confidence: 99%
“…Compared to uniaxial tests, experiments under shear and indentation have been conducted less frequently [32]. Simple shear tests on NiTi SMAs were performed early by Manach and Favier [33], while a more comprehensive study within a wider range of strain rates from 10 −4 s −1 to 10 3 s −1 was accomplished by Huang et al [34].…”
Section: Introductionmentioning
confidence: 99%